"More than Friends": Bisexual Perspectives in Roberta M. Graham's Fallen Angel and Helen Chadwick's Lofos Nymphon - Naomi Pearce (British Art Studies)
This article traces Roberta M. Graham's and Helen Chadwick's creative and loving friendship through close readings of Graham's *Fallen Angel* (1986) and Chadwick's *Lofos Nymphon* (1987), exploring how these photographic installations illustrate what Clare Hemmings has described as a "bisexual perspective". While the discourse around both artists' work thoroughly documents their male collaborators, their relationship with, and influence on, one another has remained unexamined. When and why does bisexuality disappear, and with what effects? How does partiality and in-betweenness pose problems for the present-day imperative of queer artistic production to be visible? Deploying an embodied approach that draws on interviews with Graham and research on Chadwick's archive, I narrate my longing for a bisexual genealogy through a series of "scenes" that expose the erotic and ethical terrain that often characterises such queer archival encounters. What insights does a bisexual perspective offer queer art history in its attempts to resist the discipline's normative, canonising tendencies?